2005
DOI: 10.1177/0361198105192700106
|View full text |Cite
|
Sign up to set email alerts
|

Study of Park-and-Ride Facilities and Their Use in the San Francisco Bay Area of California

Abstract: Park-and-ride lots are important support facilities for transit and ride-sharing in the San Francisco Bay Area of California. The authors designed and carried out the region's first large-scale, detailed study of park-and-ride facilities and users. Three Bay Area Rapid Transit (rail) station parking lots were also surveyed. The user survey results showed that almost all the parking users were commuters; at the freeway lots, half were transit users and the remainder were organized and casual car-poolers. Most d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Researchers concerned about this issue have made several proposals to local governments to mitigate these problems. The majority of approaches have been a complete switch from private vehicles to a more friendly transport mode (e.g., pedestrians, bicycles, public transport) [18][19][20]. However, an alternative should also exist for inhabitants who own a private vehicle and live outside the urban area, and have limited or no connection to public transport services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers concerned about this issue have made several proposals to local governments to mitigate these problems. The majority of approaches have been a complete switch from private vehicles to a more friendly transport mode (e.g., pedestrians, bicycles, public transport) [18][19][20]. However, an alternative should also exist for inhabitants who own a private vehicle and live outside the urban area, and have limited or no connection to public transport services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The general auto-orientation of most U.S. cities means that providing park-and-ride facilities can maximize the number of people who can easily get to stations (Shirgaokar and Deakin 2005;Merriman 1998). A parking facility extends the radius of a station's catchment area by several miles, and this causes an exponential expansion of the land area and population served by a given station.…”
Section: Advantages Of Park-and-ridementioning
confidence: 99%
“…The motivation for including interactions stems from recent survey research of Bay Area park-and-ride passengers that demonstrated how they generally make long trips to the central business district (Shirgaokar and Deakin 2005). The coefficients for these interactions measure how an independent variable can moderate the influence of another independent variable on the dependent variable.…”
Section: Model Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also use a disaggregate approach based on P&R user surveys. Some focus on demographic and trip characteristics of P&R users (Shirgaokar and Deakin 2005). Others include P&R as an access option to transit stations and then predict an individual's propensity to use transit based on their use of P&R facilities (Roorda, Passmore, and Miller 2009).…”
Section: Introductionmentioning
confidence: 99%